(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In this study, we explore the difficulties encountered by HR departments in the present day.Human resource management (HRM) is an approach to running a business that aims to get the most outof its employees so that they can help the firm achieve its long-term goals and objectives. This researchuses social network analysis (SNA) to examine how various HRM procedures at the Ministry of Minesand Petroleum have led to the development of specific networks. This study’s findings suggest that theexisting HRM inside public organizations in Afghanistan, especially the MoMP, exhibits certain aspectsof strategic HRM, despite the absence of a contemporary administrative structure as a result of the failedimplementation of administrative reform. This result sheds light on the notion of strategic HRM, whichhas greater potential than standard HRM to contribute to the long-term viability of the MoMP.